2012
DOI: 10.1073/pnas.1115083109
|View full text |Cite
|
Sign up to set email alerts
|

Tissue inhibitor of metalloproteinase-1 (TIMP-1) regulates mesenchymal stem cells through let-7f microRNA and Wnt/β-catenin signaling

Abstract: Tissue inhibitor of metalloproteinases 1 (TIMP-1) is a matrix metalloproteinase (MMP)-independent regulator of growth and apoptosis in various cell types. The receptors and signaling pathways that are involved in the growth factor activities of TIMP-1, however, remain controversial. RNA interference of TIMP-1 has revealed that endogenous TIMP-1 suppresses the proliferation, metabolic activity, and osteogenic differentiation capacity of human mesenchymal stem cells (hMSCs). The knockdown of TIMP-1 in hMSCs acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
96
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(111 citation statements)
references
References 45 publications
8
96
0
1
Order By: Relevance
“…43 Effects of TIMP-1 on proliferation and differentiation have been described for several cell types, including tumor cells, 44 neuronal cells, 45 and mesenchymal stem cells. 17 Interestingly, TIMP-1 was concurrently discovered as erythroid potentiating activity (EPA), 46 a factor that stimulated proliferation of human erythroid progenitors, 47 and this effect was found to be independent of protease inhibition. 48 Furthermore, the hematopoietic stem cell (HSC) compartment was shown to be functionally impaired in TIMP-1 knockout mice 49 and engraftment of HSPCs after BM transplantation was promoted by TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…43 Effects of TIMP-1 on proliferation and differentiation have been described for several cell types, including tumor cells, 44 neuronal cells, 45 and mesenchymal stem cells. 17 Interestingly, TIMP-1 was concurrently discovered as erythroid potentiating activity (EPA), 46 a factor that stimulated proliferation of human erythroid progenitors, 47 and this effect was found to be independent of protease inhibition. 48 Furthermore, the hematopoietic stem cell (HSC) compartment was shown to be functionally impaired in TIMP-1 knockout mice 49 and engraftment of HSPCs after BM transplantation was promoted by TIMP-1.…”
Section: Discussionmentioning
confidence: 99%
“…N-TIMP-1 is sufficient to inhibit almost the full spectrum of TIMP-1 substrates, 9 but lacks the cytokine domain. TIMP-1/T2G 16 and vvTIMP-1 17 carry amino acid mutations in the N-terminus that impair or abolish the capability to bind proteases but retain full signaling function. Adenoviral transduction of mice with these variants revealed that N-TIMP-1 did not increase, but rather slightly decreased the numbers of circulating neutrophils, indicating that MMP inhibition was not sufficient to induce neutrophilia.…”
Section: Timp-1 Signaling But Not Protease Inhibition Triggers Granulmentioning
confidence: 99%
See 1 more Smart Citation
“…TIMPs and MMPs play a critical role in the formation, alteration, and degradation of matrix proteins [27][28][29] . TIMP-1 can combine with most MMP active sites, thus inhibiting enzyme activity [30][31] . However, some research has found that the expression of TIMP-1 is significantly higher in the scar tissue of patients with HS than in scar tissues of patients with normotrophic scars 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, several signal transduction pathways are involved in the maintenance of the stem cell fate or in triggering differentiation processes, in particular the Wnt/ β -catenin signal transduction pathway Willert et al , 2003 ;Neth et al , 2006Neth et al , , 2007Ling et al , 2009 ;Egea et al , 2012;Peröbner et al, 2012 ). In the absence of Wnt ligands, β -catenin is degraded by the destruction complex, which is formed by axin, adenomatosis polyposis coli (APC), glycogen-synthase-kinase-3 β , and casein kinase 1 α .…”
Section: Introductionmentioning
confidence: 99%